The governance core 2.0 school boards, superintendents, and schools working together - Campbell, Davis; Fullan, Michael; Kavanaugh, Babs (Thousand Oaks, California Corwin, 2025)
"A common vision driven by a shared moral imperative. That is what this book is about. Our vision is of a governance system, school board and superintendent, working together as a cohesive, unified team with a common vision driven by a shared moral imperative. This is a dynamic, powerful role for school boards. It assumes that governance is a basic function of the organization, an integral part of the system, setting the direction of the district, assuring the achievement of strategic goals and the moral imperative, holding the district accountable and providing leadership to the community. Most importantly it is a governance system that fulfills its responsibility to all the children and the community it serves"--
Chapter 1: Moral Imperative and the Governance Core -- Chapter 2: The Governance Mindset -- Chapter 3: The Governance Mindset in Action --Chapter 4: Onboarding: Welcoming New Trustees -- Chapter 5: Governing Coherence and Synergy -- Chapter 6: The Governance Responsibilities of the Board -- Chapter 7: Governance Infrastructure -- Chapter 8: Governance Tools --Chapter 9: New Pathways.
Revised edition of: The governance core. 2019.
Includes bibliographical references and index.
Keywords: School board-superintendent relationships -- United States; School management and organization -- United States; Educational leadership -- United States